Injury patterns on child violence cases: analysis of Klaten Soeradji Tirtonegoro Hospital Emergency data - El-Ikhram, Rizkhal; Gizela, Beta Ahlam; Suriyanto, Rusyad Adi (Universitas Gadjah Mada, 2022)
Purpose: This study aims to determine the pattern of injury in cases of physical and sexual violence against children at RSUP Dr. Soeradji Tirtonegoro Klaten in 2017-2019, including what types of injuries often occur, age distribution, gender, and location of the injury. Methods: This study uses a descriptive research type with a cross-sectional research design. Data were taken using medical records belonging to Dr. Soeradji Tirtonegoro Klaten General Hospital from 2017-2019 and were conducted from May to July 2021. Results: From a total of 63 research subjects, it was found that the most violence experienced by children in the form of sexual violence was 73%. The types of physical violence injuries obtained were 6% cuts, 45.5% abrasions, and 48.5% bruises. The highest age distribution was between 10-14 and 15-17 years, each with 25 cases (39.7%). Women are the most common gender in 95% of cases. The location of most physical violence injuries was in the thorax and extremities 27.3. The location of sexual violence comes from the hymen as much as 60%. Conclusion: The most common types of injuries in cases of violence against children in the Emergency Room RSUP Dr. Soeradji Tirtonegoro in 2017 – 2019 was injured due to sexual violence—physical violence. Most types of injury come from hematomas or bruises. The highest ages were found at 10-14 years and 15-17 years. Most of the sex is experienced by girls. The most common sites of injury are injuries to the thorax and extremities. Meanwhile, the head, abdomen, and pelvis regions are followed for the other sequences. The location of sexual violence often occurs in the hymen.